Attitudes to Cannabis Use and Public Prevention Information Among Young Adults: A Qualitative Interview Study With Implications for Prevention Practice - Kvillemo, Pia; Strandberg, Anna K.; Gripenberg, Johanna (Frontiers in Public Health, 2022)
Background Cannabis use carries an increased risk of ill health and social problems, especially when initiated at a young age. Drug use is influenced by individual beliefs, knowledge, and attitudes, which are, in turn, governed by social and environmental factors. In recent years, a less restrictive attitude toward cannabis has been observed in many countries, with concerns about increased cannabis use among young people. The aim of the current study was to gain a deeper understanding of young adults' attitudes toward cannabis use and public prevention information about cannabis. Methods A qualitative interview study was conducted among 32 anonymous informants aged 18–29 years in the Stockholm region. Participants were recruited through purposeful sampling, and semi-structured in-depth interviews were conducted using a digital video calling platform. A qualitative content analysis of the interviews was performed to generate categories and codes for cannabis use and attitudes toward prevention information. Results Both cannabis users and abstainers perceived some risks with cannabis; however, for many users, the positive effects appeared to outweigh any expected harm. Furthermore, the existing public information was perceived as less credible because of an excessive focus on harm. The informants expressed a desire for neutral facts about the effects of cannabis, delivered by credible senders. Moreover, they felt that prevention information should be delivered by individuals whom young people look up to or with whom they can identify, for example, people with authority or famous people such as influencers. The informants also underlined the importance of dialogue with the target group and taking young people's experiences into account when providing information about cannabis. Conclusion Current risk awareness associated with cannabis use among young adults is insufficient to prevent them from using cannabis. Public prevention information should preferably combine a fact-based focus on risks with recognition of cannabis' short-term desired effects, delivered by credible senders with authority or those with whom young people can identify.